2021
DOI: 10.3390/ani11030813
|View full text |Cite
|
Sign up to set email alerts
|

Four Unusual Cases of Congenital Forelimb Malformations in Dogs

Abstract: Four dogs were presented with thoracic limb deformity. After clinical and radiographic examinations, a diagnosis of congenital malformations was performed for each of them. In one case, a deformity involving both the radial and ulnar side of the distal limb was observed. Based on clinical and radiological evaluations, a diagnosis of postaxial terminal longitudinal ulnar hemimelia was performed. The term ectrodactyly was used to refer different malformations characterized by skin and soft tissue separation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…In contrast, polydactyly, cardiomegaly, five thoracic vertebrae, six lumbar vertebrae and fifteen ribs, with hypoplasia of the first pair were associated with bilateral hemimelia in cats (Lockwood et al, 2009;Pisoni et al, 2012). Regarding etiology, it has been suggested that hemimeliamay be a hereditary trait in Siamese and Domestic short hair cats (Di Pietro et al, 2021). In contrast, the hemimelia recorded here was seen in a Persian cat.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In contrast, polydactyly, cardiomegaly, five thoracic vertebrae, six lumbar vertebrae and fifteen ribs, with hypoplasia of the first pair were associated with bilateral hemimelia in cats (Lockwood et al, 2009;Pisoni et al, 2012). Regarding etiology, it has been suggested that hemimeliamay be a hereditary trait in Siamese and Domestic short hair cats (Di Pietro et al, 2021). In contrast, the hemimelia recorded here was seen in a Persian cat.…”
Section: Discussioncontrasting
confidence: 62%
“…In this regard, cats with mild cases of hemimelia, do not necessarily have a bad quality of life necessitating euthanasia. Survival into adulthood with a favorable quality of life is possible (Barrand and Cornillie, 2008;Di Pietro et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Ectrodactyly is well described in humans and other species [ 12 , 13 , 14 ]. In most cases of ectrodactyly, this type of dysostosis is combined with other anomalies such as ectodermal dysplasia, cleft palate and thumb-with-three phalanges [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In humans and the dactylaplasia mouse, the pathogenesis of ectrodactyly is based on the hypothesis of a missing central ray. The combination of ectrodactyly and polydactyly, known as an ectrodactyly-polydactyly syndrome in humans [ 14 , 17 ], is a rare genetic limb malformation characterised by hypoplasia or absence of the central digital rays of the hands and/or feet. The presence of one or more unilateral or bilateral supernumerary digits on the post-axial rays ranges from hypoplastic digits without bony structures to complete duplication of a digit.…”
Section: Discussionmentioning
confidence: 99%